Association between body mass index and exacerbation frequency in patients with chronic obstructive pulmonary disease from Santa Marta - Colombia - Pedrozo-Pupo, John Carlos; Celemín-Güete, Gabriel Jesús; Campo-Arias, Adalberto (Universidad y Salud, 2019)
Introduction: Body mass index (BMI) is inversely related to the exacerbation frequency in patients with chronic obstructive pulmonary disease (COPD). However, this relationship may vary depending on the context. Objective: To quantify the association of BMI with exacerbation frequency in patients from Santa Marta-Colombia. Materials and methods: A cross-sectional study of adults with COPD. We calculated the BMIs, and the exacerbation frequencies were estimated using the Global initiative for Chronic Obstructive Lung Disease (GOLD) classification. Results: 292 patients aged between 49-95 years were included. From those, 180 (61.6%) were male, 153 (52,4%) were healthy, 21 (7,2%) showed malnutrition, and 118 (40,4%) were overweight/obese patients. The observed IMCs were between 12,8 and 40,2 (median=24,2; SD=4,5). Whereas 156 patients (53,4%) were classified as GOLD A or B (infrequent exacerbations), 136 of them (46,6%) were GOLD C of D (frequent exacerbations). 85,7% of the patients with malnutrition showed frequent exacerbations, compared to both patients with healthy weight (51,6%) and overweight/obese patients (33.1%) (OR=0,18; CI95% 0,05-0,66 for healthy weight and OR=0.08; CI95% 0,02-0,29 for overweight/obesity, both compared to patients with malnutrition). Conclusions: BMI is inversely correlated with exacerbation frequency in patients with COPD from Santa Marta-Colombia.